1999
DOI: 10.2337/diabetes.48.5.1183
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of obese diabetes in the TSOD mouse.

Abstract: The molecular pathogenesis of diabetes remains poorly understood because of the genetic complexity of the disease. One possibly effective approach to elucidate the pathogenesis is to study an animal model with a similar phenotype. The TSOD (Tsumura, Suzuki, Obese Diabetes) mouse, a newly developed animal model, exhibits both diabetes and obesity with marked hyperinsulinemia and hypertrophy of the pancreatic islets and might represent a common form of obese type 2 diabetes in humans. Phenotypic characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(91 citation statements)
references
References 8 publications
6
81
0
Order By: Relevance
“…Because plasma insulin concentrations were not altered, the Akita-derived alleles at Dbm4 appeared to confer insulin resistance that led to fasting hyperglycemia and hyperglycemia in response to glucose administration. Similar QTL analysis results were reported for TSOD mice, a T2D model established from the outbred ddY strain (Hirayama et al 1999). TSOD mice showed a suggestive linkage between plasma glucose concentrations and D15Mit63, relatively close to our LOD score peak at D15Mit233, with a recombination distance of about 0.3 cM.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Because plasma insulin concentrations were not altered, the Akita-derived alleles at Dbm4 appeared to confer insulin resistance that led to fasting hyperglycemia and hyperglycemia in response to glucose administration. Similar QTL analysis results were reported for TSOD mice, a T2D model established from the outbred ddY strain (Hirayama et al 1999). TSOD mice showed a suggestive linkage between plasma glucose concentrations and D15Mit63, relatively close to our LOD score peak at D15Mit233, with a recombination distance of about 0.3 cM.…”
Section: Discussionsupporting
confidence: 65%
“…Thus, in the region near D11Mit254, the Akita-derived alleles apparently induced insulin resistance in nondiabetic mice. A similar LOD score plot with respect to plasma glucose concentration was reported for the TSOD diabetic mouse (Hirayama et al 1999). This TSOD mouse locus (D11Mit128), named Nidd4, is separated from D11Mit254 by about only 1.0 Mb, which suggests the presence of a potential genetic modifier of T2D around Dbm2.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…14 Miura et al 12 reported that the insulinstimulated translocation of glucose transporter (GLUT)-4 from low-density microsomal membranes to plasma membranes was reduced in both the skeletal muscle and adipose tissue of TSOD mice and that the reduced insulin sensitivity was presumably owing to this impaired GLUT-4 translocation in both the skeletal muscle and adipocytes. Using a genome-wide screen for loci linked to glucose homeostasis and body weight in TSOD mice, Hirayama et al 28 mapped three quantitative trait loci involved in diabetes mellitus. The major genetic determinants of blood glucose levels, insulin levels, and body weight were identified on chromosome 11, chromosome 2, and chromosome 1 and 2, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…16,17) In our experiments, the TSOD mice showed significant accumulation of visceral fat, and developed metabolic disorders including glucose intolerance, hyperlipidemia, hypertension, hyperinsulinemia and peripheral neuropathy. This was in sharp contrast to the TSNO control group.…”
Section: Tionmentioning
confidence: 99%